Macular pigment evaluation using dual-wavelength fundus auto-fluorescence imaging - Rajs, Patrik; Liehneova, Ivana; Stranak, Zbynek (Biomedical papers, 2025)
Introduction. Macular pigment plays an important role in the reduction of oxidative stress and in preventing retinal diseases. Quick and easy measurements of the macular pigment are essential in both clinical and research settings. Dual wavelength fundus auto-fluorescence seems to be the optimal method. This study aims to investigate changes in fundus autofluorescence in patients taking daily lutein oral supplements and develop image processing methods for follow-up evaluations of the images. Methods. New devices allow us to examine fundus autofluorescence using both blue and green excitation wavelengths. This allows detection of the amount of macular pigment by subtracting these two images because the yellow pigment particles absorb blue wavelengths. We determined daily dose of 25 mg of lutein and 3 mg of zeaxanthin. Patients were followed up for 15 months at 3-month intervals. Results. During our 15-month study, we observed a positive trend in pixel lightness values, suggesting an increase in macular pigments in the foveal area. In all patients taking daily lutein supplements, the foveal index significantly increased after six months, with a median change of 0.081. We did not observe a significant change after the first three months (0.006) and only a small change between the 6th and 12th-month visits (0.012). Conclusion. With appropriate patients and procedures for capturing autofluorescence images, this is a valuable technique for macular pigment evaluation in follow-up examinations using software image post-processing and analysis with commonly available hardware. To put this into everyday practice, developing tools to automate the assessment is necessary.
Keywords: retina; macula; lutein; macular pigment; auto-fluorescence